The social-education-economy-health nexus, development and sustainability: perspectives from low- and middle-income and African countries - Marlon E. Cerf (Discover Sustainability, 2023)
Abstract The Sustainable Development Goals (SDGs) represent global action to address the challenges that impact society and nations, are inclusive, equitable, integrated, interdependent and people-centric. Some of the key SDG targets address societal issues, that include education, economic and health lags, particularly in low- and middle-income and African countries. The nexus of society, education, the economy and health, is therefore discussed and interrelated to provide perspectives on advancing development and sustainability. Being socioeconomically disadvantaged impacts access to quality education and health, limits economic activity and diminishes sustainability. Many people live in impoverished countries due to ailing economies with high unemployment. These global and pervasive challenges persist and limit the potential of people and nations. Sustainable advancement requires empowered well-educated people who contribute to economic growth and have access to quality healthcare who can contribute to greater development and sustainability. Therefore a social-education-economy-health nexus is contextualized that aligns with the SDGs and converges to support growth and sustainability, and realize social, education, economic and health value. Education, training and skilling that are relevant to address socioeconomic and health challenges are critical for development and sustainability. Strengthening the social-education-economy-health nexus will advance development and sustainability. Investment in low- and middle-income and African countries, through public–private-philanthropy partnerships to fund social, economic, education and health initiatives, will foster development and sustainability.